Faktor – Faktor Yang Mempengaruhi Impor Produk Pertanian di Indonesia - Muhammad Dzikri Almajid; Sri Ulfa Sentosa (Universitas Negeri Padang, 2022)
This study aims to determine; (1) the influence of households on imports of agricultural products to Indonesia, (2) the effect of the curve on imports of Indonesian agricultural products, (3) the effect of gross domestic product (GDP) on imports of agricultural products to Indonesia. This type of research is descriptive and associative research. The data used is secondary data in the form of times series data from 1989 to 2020. The research method uses the OLS approach, so there are several, namely: (1) Normality Test; (2) Multicollinearity Test; (3) Autocorrelation Test; (4) Autocorrelation Test; (5) Heteroscedasticity Test. The results showed that; (1) T consumption of the agricultural sector has a significant effect on imports of agricultural products to Indonesia. (2) that the exchange rate has a significant effect on imports of agricultural products to Indonesia. (3) GRDP of the agricultural sector has a significant effect on imports of agricultural products to Indonesia, (4) consumption of agricultural products, the exchange rate and GRDP of the agricultural sector together have a significant effect on imports of agricultural products to Indonesia.